Encore Moderne? (2005)
Acerca de la exposición organizada por IFA, sobre arquitectura brasilera entre 1928-2005.
Keywords: PERRIAND, CHARLOTTE; ARQUITECTURA; EXPOSICIONES; BRASIL; MOVIMIENTO MODERNO; HISTORIA